Cardiomyopathies Types and Treatments - Kirali, Kaan (IntechOpen, 2017)
Cardiomyopathies are the most featured cardiac pathologies in the twenty-first century, that threaten public health and burden healthcare budgets. This book is composed of the main topics on pathophysiology, general forms and specific types of cardiomyopathies and it also introduces new research in the field. Specific forms with or without genetic inheritance are discussed separately to attract the readers' attention on these topics. Well-known medical follow-up strategies occur ineffective at the end-stage heart failure, however, new surgical approaches can be an alternative for these patients to get a chance at the last crossroad and to improve their life quality and survival and also to gain or prolong time until possible heart transplantation.